1999
DOI: 10.1073/pnas.96.23.13363
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the copper chaperone HAH1 with the Wilson disease protein is essential for copper homeostasis

Abstract: The delivery of copper to specific sites within the cell is mediated by distinct intracellular carrier proteins termed copper chaperones. Previous studies in Saccharomyces cerevisiae suggested that the human copper chaperone HAH1 may play a role in copper trafficking to the secretory pathway of the cell. In this current study, HAH1 was detected in lysates from multiple human cell lines and tissues as a single-chain protein distributed throughout the cytoplasm and nucleus. Studies with a glutathione S-transfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
235
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 250 publications
(246 citation statements)
references
References 40 publications
7
235
0
4
Order By: Relevance
“…ATP7B plays a key role in hepatic copper excretion, by virtue of its ability to transport copper across cellular membranes at the cost of ATP hydrolysis. Within its amino terminal region, ATP7B contains six copper binding sequences, through which it receives copper by a transient copper-dependent interaction with the copper chaperone ATOX1 7,8 . Under basal conditions, ATP7B resides in the trans Golgi network (TGN), where it facilitates the incorporation of copper in cuproenzymes such as ceruloplasmin.…”
Section: Introductionmentioning
confidence: 99%
“…ATP7B plays a key role in hepatic copper excretion, by virtue of its ability to transport copper across cellular membranes at the cost of ATP hydrolysis. Within its amino terminal region, ATP7B contains six copper binding sequences, through which it receives copper by a transient copper-dependent interaction with the copper chaperone ATOX1 7,8 . Under basal conditions, ATP7B resides in the trans Golgi network (TGN), where it facilitates the incorporation of copper in cuproenzymes such as ceruloplasmin.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent modeling studies indicated that this kinked helix could be a docking site for Atox1 (Gourdon et al 2012) as well as for the 6th metalbinding domain (Arumugam & Crouzy, 2012) making the question of where Atox1 delivers the Cu ion still unresolved. Regardless, the importance of the metal-binding domains in vivo is clear: at least three disease-causing point mutations are found in the metal-binding domains of ATP7B (Hamza et al 1999).…”
Section: Moving Cu From Chaperone To Atp7a/bmentioning
confidence: 99%
“…Subsequently, this motif was found in the promotor regions of several other genes (Muller & Klomp, 2009). In support of playing a role in the nucleus, the sequence of Atox1 contains an apparent nuclear localization signal KKTGK within its C-terminal part and, although not discussed, in the initial discovery paper of Atox1 from 1999 (Hamza et al 1999), immunofluorescence of HeLa cells indicated that Atox1 was distributed throughout the cell, including the nucleus. In our work, we have also detected Atox1 in the nuclei of HeLa cells (Fig.…”
Section: Interactions With Other Proteins and New Functionsmentioning
confidence: 99%
“…Copper binding to ATP7A and ATP7B forms a key event in the catalytic cycle. An essential step in ATP7A-and ATP7B-dependent copper transport is copper delivery by the copper chaperone ATOX1 [90][91][92][93]. The importance of ATOX1 in mammalian biology is clearly illustrated by the Atox1 knockout mice that displayed a copper deficiency phenotype similar to Menkes disease [90].…”
Section: Regulation Of Copper Transport By Protein-protein Interactionsmentioning
confidence: 99%